TREATMENT OF HYPERTENSIVE PATIENTS WITH HIGH OR VERY HIGH CARDIOVASCULAR RISK. PHARMACOECONOMIC EFFICIENCY OF A TRIPLE COMBINATION THERAPY CONTAINING ANGIOTENSIN CONVERTING ENZYME INHIBITOR, CALCIUM CHANNEL BLOCKER AND STATIN - I. N. DYAKOV (Медицинский совет, 2016)
Arterial hypertension (AH) is one of the most common cardiovascular diseases and a frequent cause of cardiovascular complications and early disability. In Russia, AH of varying severity may affect about 30% of the population. [1] Hypertension is the causal factor for 27% of cardiovascular events in women and 37% in men. [2] AH accounts for about 14% of myocardial infarctions in men and 30% in women [3], 35% of ischemic strokes, 39% of chronic heart failures in men and 59% in women, and 56% of cases of chronic renal disease. [4–6]